The Quantum Gamble - Boeyens, Jan C. A. (Springer International Publishing : Imprint: Springer, 2016)
This volume, written by a highly cited author, presents the history of quantum theory together with open questions and remaining problems in terms of the plausibility of quantum chemistry and physics. It also provides insights into the theory of matter-wave mechanics. The content is aimed at students and lecturers in chemistry, physics and the philosophy of science.